Comment on: "Clinical Features, Management, and Prognosis of an International Series of 161 Patients With Limited‐Stage Diffuse Large B‐Cell Lymphoma of the Bone (the IELSG‐14 Study)". (23rd October 2014) - Hoppe, Richard; Illidge, Tim; Specht, Lena; Vogelius, Ivan; Yahalom, Joachim
Abstract : The conclusion of Ventre et al. is that patients with primary diffuse large B‐cell lymphoma (DLBCL) of bone should be treated with anthracycline‐based chemotherapy (the standard for all cases of DLBCL) with or without radiotherapy. The study suffers from several weaknesses that make the conclusion doubtful.